Studi Independent Prediksi Harga Komoditi Petani Bawang Merah Menggunakan Amazon Forecast di PT. Techno International Mandira - Arisandy, Desy; Apriani, Tri (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
The Certified Independent Study, under the Kampus Merdeka initiative and supported by the Ministry of Education, Culture, Research, and Technology (Kemendikbud Ristekdikti), fosters collaborative partnerships with key industry players. A prime example is PT. Techno International Mandira's contribution, which involves employing Amazon Forecast within Amazon Web Services for the predictive analysis of shallot farmers' commodity prices. This study centers on developing web-based predictive models to accurately forecast shallot market values. Utilizing Amazon Forecast's fully managed services, which integrate advanced machine learning algorithms, this project aims to provide vital insights into commodity pricing trends, thereby supporting shallot farmers in strategic decision-making. The methodology encompasses the application of Amazon Forecast for efficient and data-driven price prediction, demonstrating the practical utility of machine learning in agricultural economics.